Self-esteem dan resiliensi sebagai prediktor penyesuaian diri mahasiswa baru di Indonesia - Faizah, Faizah; Marmer, Farica Veronica; Aulia, Nadhirah Nurul; Rahma, Ulifa; Dara, Yuliezar Perwira (Persona:Jurnal Psikologi Indonesia, 2020)
AbstractStudents who continue their education to higher education will find a variety of changes, new challenges, demands, and greater responsibilities. This transition can put pressure on new students and negative results if they cannot pass it. The purpose of this study was to determine the role of self-esteem and resilience towards the adjustment of new students. Determination of the sample using accidental sampling technique with a sample of new students in the first semester who are actively enrolled in state or private universities (N = 673). Measuring instruments used are the Rosenberg Self-esteem Scale-Revised with reliability 0,836, Brief Resilience Scale with reliability 0,747, and Inventory of New College Student Adjustments with reliability 0,701 that have been through the process of trans adaptation. Based on the results of multiple regression tests, self-esteem and resilience are significant predictors of the adjustment of new students in a positive direction. Self-esteem is an evaluation of core self and resilience in difficult times can be a factor that increases the adjustment of new college students.Keywords: Adjustment; New College Student; Resilience; Self-esteem AbstrakSiswa yang melanjutkan pendidikannya ke perguruan tinggi akan menemukan berbagai perubahan, tantangan baru, tuntutan, dan tanggung jawab yang lebih besar. Transisi ini dapat memberikan tekanan bagi mahasiswa baru dan hasil yang negatif apabila tidak dapat melewatinya. Tujuan penelitian ini adalah untuk mengetahui peran self-esteem dan resiliensi terhadap penyesuaian diri mahasiswa baru. Penentuan sampel menggunakan teknik accidental sampling dengan sampel mahasiswa baru di semester pertama yang terdaftar aktif di perguruan tinggi negeri ataupun swasta (N = 673). Alat ukur yang digunakan adalah skala Rosenberg Self-esteem Scale-Revised dengan reliabilitas 0,836, Brief Resilience Scale dengan reliabilitas 0,747, dan Inventory of New College Student Adjustment dengan reliabilitas 0,701 yang telah melalui proses transadaptasi. Berdasarkan hasil uji regresi berganda, self-esteem dan resiliensi merupakan prediktor yang signifikan terhadap penyesuaian diri mahasiswa baru dengan arah yang positif. Self-esteem sebagai evaluasi inti diri dan resiliensi sebagai ketahanan dalam masa sulit dapat menjadi faktor yang meningkatkan penyesuaian diri mahasiswa baru.Kata kunci: Mahasiswa baru; Penyesuaian diri; Resiliensi; Self-esteem